DISEMINASI HAND SANITIZER MAMPU MENGURANGI PERTUMBUHAN MIKROBA DI SIANTAR ESTATE - Herna Febrianty Sianipar; Theresia Monika Siahaan; Mungkap Mangapul Siahaan; Maryanto Saragih (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
The COVID-19 pandemic can threaten human lives and can spread massively if there are no comprehensive preventive measures in all countries including Indonesia. Various efforts are known to be made to prevent the spread of COVID, including the use of hand sanitizers, which are antiseptic fluids capable of killing viruses, bacteria, and fungi found in the air, tools, and the human body, including hands. . The method of activities carried out in this community service is counseling using the lecture method using power point slide media which contains an explanation of the importance of a hand sanitizer and demonstrating directly with a hand swab from a community before and after using a handsanitizer and then scratching it on PDA media (Potato Dextrose Agar). The conclusion of this community service is that the community understands the importance of using a handsanitizer before carrying out activities because they see directly the growing bacteria.